LABOR FUNDS AS COMPOSITIONAL PROVIDERS OF THE INTELLECTUAL CAPITAL OF DOMESTIC MACHINE-BUILDING ENTERPRISES IN REGIONAL CUTTING: PROBLEMS AND WAYS TO SOLVING - Nahorniak , H.S. (The actual problems of regional economy development, 2019)
The article is aimed at studying the role of labor factors as important components of providing intellectual capital of domestic machine-building enterprises in a regional context, and identifies the problems and ways of solving this problem. In the conditions of modern information economy one of the most powerful driving forces of the development of civilization is the creative activity of man. The efficiency of the economy, the scientific and technical level of production, and socio-economic progress depend on the amount of knowledge accumulated by society and the effectiveness of using the country’s intellectual resources. The general tendency of the development of innovative economies under the influence of the information revolution is characterized by a new relationship between human and physical capital, in which human capital becomes a priority in economic development. Such an element of intellectual capital, as human capital, can become a competitive advantage of the country as a whole, thus also affecting individual enterprises. A special role is played by human capital, influencing the development of innovations (along with technology and capital). The development of human capital is through adequate training, training, motivation in schools, universities, companies, society, and the state. Consequently, the development of intellectual capital in machine-building enterprises is capable of increasing their competitiveness, allowing them to find new opportunities for market conquest. Strengthening the role of intellectual resources in the development of the competitiveness of mechanical engineering enterprises in the knowledge economy has led to the changing conditions and methods of creating added value: knowledge, skills of human resources (human capital), organizational and managerial capabilities of the enterprise, its competencies (structural capital) have become the main factors of creating a new value and in fact synthesized the emergence of intellectual capital, which can be interpreted as a key element of the enterprise’s competitiveness, that is, the element that forms the potential competitiveness. The essence of the concept of “intellectual capital” is revealed, author’s interpretation of the concept “intellectual capital of machine-building enterprises” is given. The issue of the influence of labor factors on intellectual capital in the machine-building industry of Ukraine is also considered. The main problems, which impede formation and development of intellectual capital in machine building of Ukraine, are determined. The recommendations for effective development of the machine-building industry on the basis of the formation and development of intellectual capital are presented. We recommended a branch partnership, which in intellectual activity is expressed in vertical or horizontal co-operation, in which machine-building enterprises combine their efforts to create a specific product for a particular industry of the industry.